Profitability determinants of financial institutions: Evidence from banks in Pakistan - Hongxing Yao; Muhammad Haris; Gulzara Tariq (International Journal of Financial Studies, 2018)
The aim of this study was to analyze the impact of bank-specific, industry-specific and macroeconomic variables on the profitability of banks in Pakistan. This study applied the two-step generalized method of momentum (GMM) system estimator on an unbalanced dynamic panel of 28 banks over the latest period 2007-2016. The robust results reveal that the bank's profitability in Pakistan is explained by size, higher solvency, financial structure, operating cost, labor productivity, market power, and economic growth. We also found an inverted U-shape relationship between banks size and profitability. Herfindahl-Hirschman Index (HHI) was applied to evaluate the impact of market power and found results in support of Structure Conduct Hypothesis. On the other hand, credit quality, operational efficiency, banking sector development, inflation, and industry concentration are found to be negatively and significantly related to the profitability of banks. Further, this study found lower profitability of banks during the government transition. The Mean comparison of profitability indicates that specialized banks (SB) in Pakistan are generating higher net interest margin (NIM) than all commercial banks (ACB). However, the empirical results of this study are robust and consistent with previous literature.
Keywords: C23; G21; G32; L2; 330; bank profitability; determinants; generalized method of momentum (GMM); Pakistan; government change